2016
DOI: 10.12659/msm.896563
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Clinical Significance of Serum CA15-3 and Carcinoembryonic Antigen (CEA) Levels in Breast Cancer Patients: A Meta-Analysis

Abstract: BackgroundBreast cancer is the most common malignant cancer in women worldwide. The tumor markers Cancer Antigen 15-3 (CA15-3) and Carcinoembryonic Antigen (CEA) are frequently used for screening and monitoring breast cancer.Material/MethodsWe conducted a meta-analysis of 13 published case-control studies to assess the associations between serum levels of CA15-3 and CEA with breast cancer susceptibility, including 1179 cases and 493 controls. The analyses were performed on malignant tumor and benign tumor, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 20 publications
5
40
0
4
Order By: Relevance
“…The results of our study indicated that abnormal high CA153 level significantly increased the risk of bone metastases in breast cancer. And the cut-off value of it was 23.25 U/ml in the present study, which was reported to be ranged from 22 to 60 u/ml in previous studies 17, 18 . In line with Wojtacki et al .…”
Section: Discussionsupporting
confidence: 58%
“…The results of our study indicated that abnormal high CA153 level significantly increased the risk of bone metastases in breast cancer. And the cut-off value of it was 23.25 U/ml in the present study, which was reported to be ranged from 22 to 60 u/ml in previous studies 17, 18 . In line with Wojtacki et al .…”
Section: Discussionsupporting
confidence: 58%
“…In our study, 100% of all eligible patients were monitored. Previous studies have profiled a small number of genes (i.e., [2][3][4][5][6][7][8][9][10][11][12][13][14] to determine the personalized variants for tracking; however, only 57% to 78% of women have any trackable mutations using such an approach (16,19,20). In our cohort, only 33 of 49 (67%) patients had one or more driver mutations identified in their exome profile, indicating that 16 of 49 patients in this study would not have been able to be monitored using a predetermined gene panel approach based on driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, imaging tests such as mammography, MRI, and PET/CT often suffer from significant false-negative and false-positive results (8)(9)(10). Biochemical methodologies such as serum levels of cancer antigen 15-3 (CA 15-3) have limited sensitivity and accuracy in detecting micrometastases (11)(12)(13) and have not been widely incorporated into clinical guidelines (14). Therefore, there is a compelling need to develop more sensitive technologies capable of detecting preclinical metastases and identifying patients with disease recurrence earlier.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, changes in the blood composition are often observed starting from an early stage. Tumor markers are often correlated with progression and they have been reported to change following recurrence before other symptoms can be detected using different tests [6][7][8]. Carcinoembryonic antigen (CEA) and cancer antigen (CA15-3) are commonly used as tumor markers for breast cancer.…”
Section: Introductionmentioning
confidence: 99%